2019
DOI: 10.1080/00405000.2019.1632627
|View full text |Cite
|
Sign up to set email alerts
|

A cross-national study of young female consumer behaviour, innovativeness and apparel evaluation: China and India

Abstract: In order to advance our knowledge about consumers' shopping behaviour and preferences in two emerging markets (China and India), the current study was undertaken to investigate (1) apparel consumers' shopping behaviour; (2) the effect of consumer innovativeness, and (3) the salient impact of apparel evaluative cues. An online self-administered survey consisted of shopping behavioural questions, the Domain Specific Innovativeness (DSI) scale, twelve apparel cues, and demographic questions were used for this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…For instance, Chao, Reid, and Mavondo (2012) highlighted how domain‐specific innovativeness rather than a consumer's innate innovativeness is the main driver for the adoption of very new products, in the context of electronic products. Rahman, Chen, Fung, and Kharb (2020) suggested that fashion innovators tend to spend more money on new clothes compared with non‐innovators. Truong (2013) found a positive effect of CI on the attitude to service‐based innovation.…”
Section: Theoretical Foundation and Development Of Hypothesesmentioning
confidence: 99%
“…For instance, Chao, Reid, and Mavondo (2012) highlighted how domain‐specific innovativeness rather than a consumer's innate innovativeness is the main driver for the adoption of very new products, in the context of electronic products. Rahman, Chen, Fung, and Kharb (2020) suggested that fashion innovators tend to spend more money on new clothes compared with non‐innovators. Truong (2013) found a positive effect of CI on the attitude to service‐based innovation.…”
Section: Theoretical Foundation and Development Of Hypothesesmentioning
confidence: 99%
“…Extrinsic cues are relatively easy to process, interpret, and understand, whereas intrinsic cues involve judging the physical properties of a product, which requires technical/practical knowledge and evidence from earlier consuming experiences. According to Swam and Combs [38], intrinsic cues can be further divided into psychic/appearance cues and physical/performance cues, with psychic utility being associated with aesthetic and hedonic aspects of a product, such as style and colour, whereas physical utility is associated with functional and utilitarian aspects such as durability and comfort [39]. It is important to note that the "product attribute" and "product cue" are used interchangeably in this article.…”
Section: Product Cues Classifications and Typologiesmentioning
confidence: 99%
“…According to some studies [88,95], the measures of DSI scale are more reliable and predictive for the adoption of new products as compared to global innovativeness. In addition, many studies [39,[96][97][98] demonstrated that the DSI scale was suitable for measuring consumer innovativeness in a specific product domain such as apparel. Therefore, the DSI was adopted for the current study.…”
Section: Consumer Innovativeness and Domain-specific Innovativeness (Dsi)mentioning
confidence: 99%
See 2 more Smart Citations